Base referencial para o povoamento de repositórios institucionais: coleta automatizada de metadados da Plataforma Lattes - Matias, Mesailde Souza de Oliveira (2015)
Open institutional repositories (IR) have became a major instrument for providing open access to global scientific production. In addition to providing scientific documents, IR can be used to fulfill institutional interests of the institution, such as promoting the storage of documentation, preserving institutional memory and also bringing worldwide exposure to its production. The implementation of an IR, however, depends on a number of activities, where one of the major challenges is populating it with data. In order to find solutions to improve the process of populating an IR, the aim of this work was to develop a system to automatically extract metadata from the Lattes Platform, inserting this metadata in a reference database, regarded as an intermediate step for populating the IR. Besides easing the submission process, the reference base will be able to support effective marketing campaigns to foster the auto-archival of scientific works. Our approach consists of a qualitative research, developed through action research, within the Federal University of São Carlos – UFSCar. The achieved results comprised the development of a collection of automated solutions essential for gathering and handling metadata to be imported by DSpace. The solution here proposed can be implemented by any institution, with or without an IR, strongly contributing to maximize scientific communication by automating part of the process of implementing and maintaining institutional repositories.